2022
DOI: 10.14202/vetworld.2022.168-172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the 5' untranslated regions of the HSP70 gene in Indonesian cattle populations

Abstract: Background and Aim: Heat shock proteins (HSPs) are a group of proteins that play a significant role in protecting cells against cellular stress. HSP70 is a conserved, sensitive, and abundant gene associated with heat stress's physiological adaptability. The objective of this study was to reveal the polymorphisms of the partial sequences of the HSP70 gene (5' untranslated region [UTR]) in seven cattle populations in Indonesia. Materials and Methods: Polymerase chain reaction products (551 bp) of the HSP70 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Among these SNPs, SNP G1045A, T1134C, and T1204C have been associated with the serum concentration of T3 and IGF-I and body condition [ 47 , 48 ], while the SNP A1125C was associated with calving percentages in crossbred Brahman cows [ 48 ]. The SNP G1076A identified by Prihandini et al [ 46 ] in Indonesian cattle breeds was also observed in South African Nguni crossbred cattle [ 49 ]. Six SNPs in the HSP70 gene, including G1045A, G1117A, A1125C, G1128T, T1134C, and T1204C, have been identified in some cattle populations from different countries [ 46 , 50 52 ].…”
Section: Candidate Genes For Thermotolerancementioning
confidence: 85%
See 2 more Smart Citations
“…Among these SNPs, SNP G1045A, T1134C, and T1204C have been associated with the serum concentration of T3 and IGF-I and body condition [ 47 , 48 ], while the SNP A1125C was associated with calving percentages in crossbred Brahman cows [ 48 ]. The SNP G1076A identified by Prihandini et al [ 46 ] in Indonesian cattle breeds was also observed in South African Nguni crossbred cattle [ 49 ]. Six SNPs in the HSP70 gene, including G1045A, G1117A, A1125C, G1128T, T1134C, and T1204C, have been identified in some cattle populations from different countries [ 46 , 50 52 ].…”
Section: Candidate Genes For Thermotolerancementioning
confidence: 85%
“…The SNP G1076A identified by Prihandini et al [ 46 ] in Indonesian cattle breeds was also observed in South African Nguni crossbred cattle [ 49 ]. Six SNPs in the HSP70 gene, including G1045A, G1117A, A1125C, G1128T, T1134C, and T1204C, have been identified in some cattle populations from different countries [ 46 , 50 52 ]. Of the six SNPs, SNP G1128T has been associated with cell viability and gene expression of the HSP70.1 gene in Holstein cattle, in which heterozygous animals showed higher cell viability (p<0.05) and gene expression (p<0.001) compared to homozygous GG [ 50 ].…”
Section: Candidate Genes For Thermotolerancementioning
confidence: 85%
See 1 more Smart Citation
“…The amplification conditions were as follows initial denaturation (95C for 5 mins), denaturation (95C for 45 sec with 35 cycles), annealing (60C for 45 sec), extension (72C for 60 sec) and final extension (72C for 5 mins). The PCR products were sequenced employing ABI 310 xL Genetic Analyser (Applied Biosystems, Inc) referred to Ansori et al (2021) and Prihandini et al (2022).…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Since livestock producers in Indonesia rely heavily on cattle for their revenue, cattle are one of the most essential livestock products (Dakhlan et al, 2022;Kuswati et al, 2022;Pakpahan et al, 2022;Prihandini et al, 2022;Sudrajad et al, 2022). The productivity of Indonesian livestock, especially local cattle, is still relatively low and is a major problem that must be resolved immediately (Mayulu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%